Improved production of ethanol using bagasse from different sorghum cultivars. (January 2015) - Nasidi, Muhammad; Agu, Reginald; Deeni, Yusuf; Walker, Graeme
Abstract: For improved production of ethanol from whole sorghum residues, physico-chemical compositions and fermentation characteristics of the substrates are important factors to consider. In the present study, Nigerian sorghum cultivars SSV2, KSV8 and KSV3 were grown under rain-fed conditions without chemical fertilization in Kano state, Nigeria. On harvest, the whole sorghum residues (bagasse) comprising crushed stalks, leaves, panicles and peduncles were collected for further processing. Bagasse samples, which had different macromolecular composition and carbohydrate pasting properties, were pre-treated with dilute sulphuric acid at 75 °C followed by enzymatic hydrolysis and sequential detoxification by Ca(OH)2 over-liming and charcoal filtration. Hydrolysate samples were subsequently fermented with the yeasts, Saccharomyces cerevisiae and Pachysolen tannophilus . Sugar consumption, carbon dioxide evolution and ethanol production were shown to vary depending on the sorghum cultivar type. While KSV3 yielded most favourable biomass of 37 t ha −1 (dry basis), bagasse from cultivar SSV2 yielded the most favourable level of sugars (69 g/100 g) after enzymatic hydrolysis, and also consistently exhibited improved fermentation performance. Detoxification of pre-treated sorghum bagasse to remove potential yeast inhibitors resulted in improvement in ethanol yield, with 23 g L −1 ethanol (representing 72% of theoretical yield) being achieved from SSV2 bagasse following fermentation with P. tannophilus without exogenous nutrient supplementation. Our findings reveal that the choice of sorghum cultivar is important when converting bagasse to ethanol, and further that pretreatment with dilute acid at moderate temperature followed by detoxification improves fermentation kinetics and ethanol yield. Highlights: The choice of sorghum cultivar is important when converting bagasse to ethanol. Pretreatment of bagasse with dilute acid at 70 °C increases ethanol yields. Further detoxification of hyrolysates improves fermentation and ethanol yields. Better fermentation with P. tannophilus than S. cerevisiae without supplementation. Better ethanol yield in the context of economic and environmental sustainability.